Modelling and Simulation of Variable Frequency Synchronous DC-DC Buck Converter - Jeya Selvan Renius; K. Vinoth Kumar; Arnold Fredderics; Raja Guru; Sree Lakshmi Nair (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this paper, novel small-signal averaged models for dc–dc converter operating at variable switching frequency are derived. This is achieved by separately considering the on-time and the off-time of the switching period. The derivation is shown in detail for a synchronous buck converter. The Enhanced Small Signal (ESSA) Model is derived for the synchronous buck converter. The equivalent series inductance (ESL) is also considered in this modelling. The buck converter model is also simulated in MATLAB and the result is also presented.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6472